Pre-employment Health Examinations: Evidence and Implications for Practice in Thailand - Krittin Nakaphadungrat; Supakorn Chansaengpetch; Narongpon Dumavibhat; Tirathat Virojskulchai; Nantapong Chansaengpetch (Srinagarind Medical Journal, 2026)
Background and objective: Pre-employment health examinations are widely used, however, their effectiveness in preventing adverse occupational health outcomes remains in question. Therefore, this study aimed to examine the evidence on the effectiveness of pre-employment and pre-placement assessments and to consider their implications for practice, with particular reference to Thailand. Methods: This study is a narrative review synthesizing evidence from studies identified through database searches (PubMed and Scopus), focusing on effectiveness, predictive value, and implications of pre-employment and pre-placement assessments. Results: Overall, current evidence is insufficient to support a routine pre-employment examination in reducing occupational injury, illness, or sickness absence. Some evidence suggests that assessments focused on specific job risks may be more appropriate. Conclusions: A targeted, risk-based approach is more appropriate than routine screening. In Thailand, a gap exists between policy and practice. Further research is required to support evidence-based occupational health policies.